On a problem of lower limit in the study of nonresonance. (1997) - Anane, A.; Chakrone, O.
Abstract : We prove the solvability of the Dirichlet problem{ − Δ p u = f ( u ) + h       in       Ω,                             u = 0                                           on     ∂ Ω for every givenh, under a condition involving only the asymptotic behaviour of the potentialF off with respect to the first eigenvalue of thep -LaplacianΔ p . More general operators are also considered.